HUBUNGAN PERSEPSI KESELAMATAN DAN KESEHATAN KERJA (KKK) DENGAN PENGGUNAAN MASKER PADA ANGGOTA KEPOLISIAN LALU LINTAS DI POLRESTA DENPASAR - Pramita Dewi (Coping: Community of Publishing in Nursing, 2014)
From the monitoring of the Ministry of Environment through the Air Quality Monitoring Stations (AQMS), out of ten major cities in Indonesia, six of them were categorized of having polluted air. Air quality parameter (total of dust), from four samplings on the streets of Denpasar showed that the dust concentration from these places were above environmental quality standards. The high CO level in the blood could lead to physiological disorders of organs, especially the lungs. One of the vulnerable groups exposed to CO was the policemen on daily traffic duty. It could be resolved by using Personal Protective Equipment (PPE) such as masks to prevent respiratory tract disease. The research design was analytic observational. The subject approach was cross sectional, samples were taken from 41 traffic police officers in Denpasar Police who are selected through random sampling. The data were obtained by filling perception questionnaires and the use of masks by traffic police officers in Denpasar Police. From Chi square test, the results obtained is p=0.003 which was lower than the value of alpha (? = 0.05 level). It was match with the hypothesis, if p <? (0.05), then Ho could be rejected, it showed that there was a significant relationship between the KKK perception with the use of masks by traffic police officers in Denpasar Police. It could be concluded that if traffic police officers had better perception on the use of masks in the KKK, the use of masks among traffic police officers would be increasing. Thsuggestion that can be given for the institution is to conduct healh education and improve specific protection of mask usage among traffic police officers.